Inovatif Rangkaian Bunga Tangan untuk Pengantin Barat - Nurulisma Saputri; Alfida Khoirunnisa (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
The bridal hand bouquet in Western weddings is an important element symbolizing the sanctity of the marriage. The hand bouquet serves as an accessory that complements the appearance of the bride and portrays her as the queen on her special day. This study aims to explain the innovative process of arranging Hologram Flower Bouquets, Rattan Flower Bouquets, and Coconut Flower Bouquets, as well as to validate the product of the book